High Tech Concrete: Where Technology and Engineering Meet Proceedings of the 2017 fib Symposium, held in Maastricht, The Netherlands, June 12-14, 2017 (Springer International Publishing, 2018)
This book contains the proceedings of the fib Symposium "High Tech Concrete: Where Technology and Engineering Meet", that was held in Maastricht, The Netherlands, in June 2017. This annual symposium was organised by the Dutch Concrete Association and the Belgian Concrete Association. Topics addressed include: materials technology, modelling, testing and design, special loadings, safety, reliability and codes, existing concrete structures, durability and life time, sustainability, innovative building concepts, challenging projects and historic concrete, amongst others. The fib (International Federation for Structural Concrete) is a not-for-profit association committed to advancing the technical, economic, aesthetic and environmental performance of concrete structures worldwide.